Fabrication of solid CH-CD multilayer microspheres for inertial confinement fusion - Meifang Liu; Xing Ai; Yiyang Liu; Qiang Chen; Shuai Zhang; Zhibing He; Yawen Huang; Qiang Yin (Matter and Radiation at Extremes, 2021)
Deuterated polymer microspheres can be used as a neutron source in conjunction with lasers because thermonuclear fusion neutrons can be produced efficiently by collisions of the resulting energetic deuterium ions. A new type of solid deuterated polymer microsphere with a carbon hydrogen–carbon deuterium (CH-CD) multilayer has been designed for preparing the target for inertial confinement fusion (ICF) experiments. To fabricate these solid CH-CD multilayer microspheres, CH beads are first fabricated by a microfluidic technique, and the CD coating layer is prepared by a plasma polymerization method. Both polystyrene (PS) and poly(α-methylstyrene) (PAMS) are used as the material sources for the CH beads. The effects of the PS and PAMS materials on the quality of the solid CH beads and the resulting CH-CD multilayer polymer microspheres are investigated. The solid PS beads have better sphericity and a smoother surface, but large vacuoles are observed in solid PS-CD multilayer microspheres owing to the presence of residual fluorobenzene in the beads and a glass transition temperature of the solid PS beads that is lower than the temperature of plasma polymerization. Therefore, solid PAMS beads are more suitable as a mandrel for fabricating solid CH-CD multilayer polymer microspheres. Solid CH-CD multilayer microspheres with specified size have been successfully prepared by controlling the droplet size and the CD deposition rate and deposition time. Compared with the design value, the diameter deviation of the inner CH beads and the thickness deviation of the CD layer can be controlled within 20 µm and 2 µm, respectively. Thus, an approach has been developed to fabricate solid CH-CD multilayer microspheres that meet the physical design requirements for ICF.